In Vivo Biological Effects of Marine Biosilica on a Tibial Bone Defect in Rats - Cruz,Matheus de Almeida (2020)
Abstract Research on biomaterials of natural origin has gained prominence in the literature. Above all, marine sponges, due to their architecture and structural components, present a promising potential for the engineering of bone tissue. In vitro studies demonstrate that a biosilica of marine sponges has osteogenic potential. However, in vivo works are needed to elucidate the interaction of biosilica (BS) and bone tissue. The objective of the study was to evaluate the morphological and chemical characteristics of BS compared to Bioglass (BG) by scanning electron microscopy (SEM) and X-ray dispersive energy (EDX) spectroscopy. In addition, to evaluate the biological effects of BS, through an experimental model of tibial bone defect using histopathological, histomorphometric, immunohistochemical (IHC) and mechanical tests. SEM and EDX demonstrated the successful extraction of BS. Histopathological analysis demonstrated that Control Group (GC) had greater formation of newly formed bone tissue compared to BG and BS, yet BG bone neoformation was greater than BS. However, BS showed material degradation and granulation tissue formation, with absence of inflammatory process and formation of fibrotic capsule. The results of histomorphometry corroborate with those of histopathology, where it is worth emphasizing the positive influence of BS in osteoblastic activity. IHQ demonstrated positive VEGF and TGF-β immunoexpression for GC, BS and BG. In the mechanical test no significant differences were found. The present results demonstrate the potential of BS in bone repair, further studies are needed other forms of presentation of BS are needed.